2021
DOI: 10.21511/ppm.19(4).2021.14
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and quality of work life: A mediation model of trust climate

Abstract: This study aims to investigate the impact of managers’ transformational leadership on employees’ quality of work life through the mediation effect of firms’ climate of trust in the hospitality industry. The study was conducted with operational employees working in three-star hotels in Bangladesh. Data were gathered from 186 respondents by a structured questionnaire and analyzed by SPSS 21 and SmartPLS 3.0 software. To test the hypothesized model, the study used a partial least squares structural equation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Third, this study found a substantial impact of teams' climate of trust on the hotel operational employees' quality of work life. This finding corroborates the results of prior studies revealing that a workplace with an atmosphere of shared and mutual trust can improve the peace and happiness of people's work lives (Akter et al, 2021;Blomeke et al, 2015;Jiang & Probst, 2015). Finally, the findings revealed a mediation effect of the team's trust climate in the relationship between hotels' organizational justice and the quality of operational employees' work life in the Bangladeshi hotel industry.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Third, this study found a substantial impact of teams' climate of trust on the hotel operational employees' quality of work life. This finding corroborates the results of prior studies revealing that a workplace with an atmosphere of shared and mutual trust can improve the peace and happiness of people's work lives (Akter et al, 2021;Blomeke et al, 2015;Jiang & Probst, 2015). Finally, the findings revealed a mediation effect of the team's trust climate in the relationship between hotels' organizational justice and the quality of operational employees' work life in the Bangladeshi hotel industry.…”
Section: Discussionsupporting
confidence: 89%
“…QWL is "employee satisfaction with a variety of needs through resources, activities, and outcomes stemming from participation in the workplace" (Sirgy et al, 2001). They emphasize the significance of the individuals' QWL on their overall (professional and personal) life (Akter et al, 2021). As stated by Razak et al (2016), the continuous implementation of QWL approaches can balance people's personal and professional life, thereby, making them feel happy with their overall life (Sirgy et al, 2001).…”
Section: Quality Of Work Lifementioning
confidence: 99%
See 3 more Smart Citations